Comparative Study of Y123 Superconductors Synthesized Under Open Air and Oxygen Flow Conditions - Kamarudin, Aliah Nursyahirah; Kechik, Mohd Mustafa Awang; Khairudin, Muhammad Azri; Kien, Chen Soo; Pah, Lim Kean; Shabdin, Muhammad Kashfi; Shaari, Abdul Halim (Balai Publikasi Indonesia, 2025)
YBa₂Cu₃O₇₋δ (Y123) superconductors is a widely studied high-temperature superconductor due to its high critical temperature, Tc and strong flux pinning properties. In this study, Y123 samples were synthesized via a thermal treatment method under two sintering conditions which were open air and oxygen flow. Structural, microstructural, and superconducting properties were evaluated using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and AC susceptibility measurements. XRD analysis revealed that all Y123 samples exhibited predominantly Y123 phase with orthorhombic structure, with minor secondary phases. The Y123 sample prepared in an open-air condition exhibited larger grain size (0.698 µm), lower porosity, and fewer impurities compared to sample prepared in the oxygen flow condition. AC susceptibility showed a higher Tc-onset exhibited at 92.1 K in the open-air sample, indicating better grain connectivity. These results suggest that open-air sintering offers a simpler, cost-effective route for enhancing Y123 superconductor performance.